Identification of copy number variations among fetuses with ultrasound soft markers using next-generation sequencing - Jing Wang (Nature Portfolio, 2018)
Abstract A prospective analysis investigating the associations between pathogenic copy number variations (pCNVs) and ultrasound soft markers (USMs) in fetuses and evaluating the clinical value of copy number variation sequencing (CNV-seq) in such pregnancy studies was carried out. 3,398 unrelated Chinese women with singleton pregnancies and undergone amniocentesis at 18–36 weeks of gestation for fetal CNV-seq were included. According to the prenatal fetal ultrasound screening results, the samples were divided into 3 groups: normal ultrasound (n = 2616), solitary USM (n = 663), and two or more USMs (n = 119). CNV-seq was performed successfully using all samples. The prevalence of pCNVs in fetuses with normal ultrasound and USMs was 3.03% (79/2616) and 2.94% (23/782), respectively. The risk of segmental aneuploidies was significantly higher in the two or more USMs group (5/119, 4.20%) than in the normal ultrasound (27/2616, 1.04%) or solitary USM (9/663, 1.36%) groups (p = 0.002 and p = 0.031, respectively). Assuming that the resolution of karyotyping is ~5 Mb, a cytogenetic analysis would miss 33 of 102 (32.35%) pCNVs in these samples. Our results suggest an association between pCNVs and fetal USMs; multiple USMs indicate an increased risk of fetal segmental aneuploidies. In prenatal diagnostic testing, CNV-Seq identified additional, clinically significant cytogenetic information.